A convergence analysis of the ADM and an application - Kaya, D; Inan, IE (Elsevier Science Inc, 2005)
In this paper by considering the decomposition scheme, we solve the modified Korteweg-de Vries equation (MKdV for short) for the initial condition. We prove the convergence of Adomian decomposition method (ADM) applied to the MKdV equation. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: the decomposition method; modified Korteweg-de Vries equation; the self-canceling noise terms; the convergence of Adomian decomposition method